Esophageal Dilatation in Patients with Esophageal Stricture Formation due to Corrosive Intake - Clinical Experience of Thoracic Surgery Department at A Tertiary Care Center - Sultan Ahmed, Tayyeba Kiran, Asia Rabbani, Rizwan Sadiq, Muhammad Abbas Zafar, Usama Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Assessment of the outcome of esophageal dilatation in patients with esophageal stricture formation due to corrosive intake experienced at a tertiary healthcare facility in order to devise a better management plan for such patients. Study design: Retrospective Study Study setting: Sheikh Zayed Medical College/Hospital, Rahim Yar Khan. Study duration: January 2018-June 2021 Methodology: A total of 19 subjects who presented with esophageal stricture formation due to corrosive intake were taken as study subjects. The location of involved mucosa, number of dilatation sessions done, level of symptomatic relief and recurrence rates were assessed for these study subjects. Then the data was gathered and analyzed with the help of SPSS Version. 21. Results: This study comprising of 19 patients who had esophageal stricture formed due to corrosive intake and they underwent esophageal dilatation for it. The age range for the subjects came out to be 5-40 years (Mean= 2.89±8.81). Male to female ratio came out to be 7(36.8%) vs 12(63.2%) respectively. Among these study subjects, 15(78.9%) subjects gave history of an acid ingestion while only 4(21.1%) had a history of alkali ingestion. Majority of them showed relief in response to esophageal dilatation and with low recurrence rates. Conclusion: Esophageal dilatation with bougies is one of the safest, less invasive, and efficient method for the effective management of esophageal stenosis/ stricture formation after corrosive intake that needs to be emphasized specially in healthcare centers which lack specialized departments dealing with more invasive surgical procedure and facilities.